Civil society and global copyright reform advocacy: incoherent frames as missed opportunities?. (1st March 2014) - Marcellin, Sherry S.; Kawooya, Dick
Abstract : After almost a decade of civil society (CS) efforts aimed at reforming the global intellectual property (IP) system, this study examines whether the paucity in global copyright reform is a result of the failure by civil society to mobilise around an explicit or coherent frame. While previous episodes of global intellectual property rights (IPR) reform advocacy involving CS were effectively contested under a human rights frame, there have been less successful framing attempts in the space of copyright reform advocacy. Using semi-structured interviews with key civil society stakeholders involved in the reform of the global copyright system, the study explores possible explanations for this lapse in framing in copyright reform advocacy. It also questions the extent to which framing has been an intelligible lens through which to understand the success or failure of global IPR advocacy. It reveals that frame analysis does not comprehensively capture success or failure in global IPR policymaking. Lastly, the study looks at problems with civil society and what these mean for copyright reform and ultimately the future of the global IPR system.